A multicentre, randomized, parallel group, superiority study to compare the clinical effectiveness and costeffectiveness of external frame versus internal locking plate for complete articular pilon fracture fixation in adults. (2021) - Flett, L.; Adamson, J.; Barron, E.; Brealey, S.; Corbacho, B.; Costa, M. L.; Gedney, G.; Giotakis, N.; Hewitt, C.; Jones, J. Hugill-; Hukins, D.; Keding, A.; et al.
No abstract available